3D analysis of synaptic vesicle density and distribution after acute foot‐shock stress by using serial section transmission electron microscopy. (22nd August 2016) - KHANMOHAMMADI, M.; DARKNER, S.; NAVA, N.; NYENGAARD, J.R.; WEGENER, G.; POPOLI, M.; SPORRING, J.
Summary: Behavioural stress has shown to strongly affect neurotransmission within the neocortex. In this study, we analysed the effect of an acute stress model on density and distribution of neurotransmitter‐containing vesicles within medial prefrontal cortex. Serial section transmission electron microscopy was employed to compare two groups of male rats: (1) rats subjected to foot‐shock stress and (2) rats with sham stress as control group. Two‐dimensional (2D) density measures are common in microscopic images and are estimated by following a 2D path in‐section. However, this method ignores the slant of the active zone and thickness of the section. In fact, the active zone is a surface in three‐dimension (3D) and the 2D measures do not accurately reflect the geometric configuration unless the active zone is perpendicular to the sectioning angle. We investigated synaptic vesicle density as a function of distance from the active zone in 3D. We reconstructed a 3D dataset by estimating the thickness of all sections and by registering all the image sections into a common coordinate system. Finally, we estimated the density as the average number of vesicles per area and volume and modelled the synaptic vesicle distribution by fitting a one‐dimensional parametrized distribution that took into account the location uncertainty due to section thickness. Our results showed a clear structural difference in synaptic vesicle density and distribution between stressed and control group with improved separation by 3D measures in comparison to the 2D measures. Our results showed that acute foot‐shock stress exposure significantly affected both the spatial distribution and density of the synaptic vesicles within the presynaptic terminal.